Letter from Mícheál Ó Coileáin [Michael Collins] to Florence O’Donoghue, acknowledging receipt of various communications and proposing Dick Mulcahy or M. Staines to give a lecture - Collins, Michael, 1890-1922; O'Donoghue, Florence, 1895-1967 (1919)
States that "the Count" may be abroad and hence unavailable for the lecture.
Keywords: Mulcahy, Richard, -- 1886-1971; Staines, Michael, -- 1885-1955; Plunkett, George Noble, -- Count, -- 1851-1948; Irish Republican Army; Ireland -- History -- 1910-1921